(untitled) (Experimental biology, 2016)
TOR kinase is present in most eukaryotic species and plays a key role in the regulation of growth and development of organisms and the formation of metabolic response of the cells to the action of various stress factors. Unlike animals, the growth of plants largely depends on changes in external conditions. Therefore, to maintain cellular homeostasis they should be adapted to a plurality of endogenous and exogenous signals originating from biotic and abiotic stresses. In this short review the possible biochemical and physiologic mechanisms of plant adaptation to salt stress and the role of abscisicacid in regulation of TOR signaling pathways are discussed.